Designing software architectures a practical approach - Cervantes, Humberto 1974-; Kazman, Rick (Addison-Wesley Professional, 2024)
Learn how to create successful architectural designs and improve your current design practices! Designing Software Architectures, 2nd Edition, provides a practical, step-by-step methodology for architecture design that any professional software engineer can use, with structured methods supported by reusable chunks of design knowledge and rich case studies that demonstrate how to use the methods. The Attribute-Driven Design method may not have changed since this book's first printing, but almost everything else about the industry has. In this newly updated edition, you will find new chapters on supporting business agility through API-centric design, deployability, cloud-based solutions, and technical debt in design. Humberto Cervantes and Rick Kazman illuminate best practices for how architects should design complex systems so you can make design decisions in systematic, repeatable, and cost-effective ways. This book will help you become a better, more confident designer who can create high-quality architectures with ease.
Includes index
Keywords: Software architecture; Big data; Architecture logicielle